2010
DOI: 10.22358/jafs/66300/2010
|View full text |Cite
|
Sign up to set email alerts
|

Carcass quality characteristics of Hair Goat and Saanen × Hair Goat crossbred kids from intensive production system

Abstract: The aim of this study was to investigate the effects of crossbreeding indigenous Hair Goat with Saanen on carcass quality characteristics of kids under an intensive production system. Twenty four male kids from purebred Hair Goat and Saanen x Hair Goat (F, and B { ) crossbred genotypes were weaned at 75-80 days of age and fattened for 56 days. Slaughter weights were 17.42,18.22 and 16.79 kg and chilled carcass weights were 6.49, 7.29 and 6.69 kg for Hair Goat, ¥ { and B,, respectively. The organ weights, dress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
9
3
1
Order By: Relevance
“…Carcass measurements of Hair goat kids recorded in this study were higher than the values reported by Yilmaz et al (21) and were generally similar to the findings of Şimşek and Bayraktar (9), with the exception of leg circumference, which was found to be relatively higher in our study.…”
Section: Carcass Measurementssupporting
confidence: 90%
See 3 more Smart Citations
“…Carcass measurements of Hair goat kids recorded in this study were higher than the values reported by Yilmaz et al (21) and were generally similar to the findings of Şimşek and Bayraktar (9), with the exception of leg circumference, which was found to be relatively higher in our study.…”
Section: Carcass Measurementssupporting
confidence: 90%
“…Proportions of lean tissue (53.7%-56.8%) obtained in this study were similar to findings reported by Yalçıntan et al (22) and Toplu et al (25) for Hair kids, but lower than values reported by Yilmaz et al (21) and higher than the proportions reported by Daskiran et al (20) with Norduz kids. Proportions of lean tissue were lower than those reported in some other studies (18,26).…”
Section: Dissected Tissue Proportionssupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, many researchers also reported that carcass fatness increased, whereas the percentage of bone decreased with slaughter weight of kids (Marichal et al 2003, Zimerman et al 2008, Dhanda et al 2003, Peña et al 2007). The higher fat content and the lower muscle content was obtained in the present study than those (5 % fat, 61-63 % muscle) recorded by Yilmaz et al (2010) for Hair, Saanen × Hair Goat F 1 and Saanen × Hair Goat B 1 kids slaughtered at 17-18 kg under intensive rearing conditions. This might be because their analyses were performed on the leg, where fat depots were significantly lower than in whole carcass.…”
Section: Resultscontrasting
confidence: 51%